Comparison of Student Learning Outcomes Using Digital and Conventional Learning Media in Senior High School - Yunita Putri Ramdani; Omy Aulia Syabiani; Nur Marsha Ivandy; Nurul Inayah (Indonesian Journal of Educational Innovation, 2025)
The integration of digital technology in education has become a strategic necessity to improve student learning outcomes in the digital era. This study aimed to compare the effectiveness of digital and conventional learning media in enhancing student achievement among seventh-grade junior high school students. A quasi-experimental research design with a pretest-posttest control group approach was employed. Sixty students were purposively selected and divided equally into two groups: an experimental group and a control group. Data were collected using a multiplechoice test to measure learning outcomes and analyzed using paired sample t-tests and independent sample t-tests to determine within-group and between-group differences. The results showed that the group taught using digital learning media achieved significantly higher posttest scores (M = 84.7) compared to the group taught using conventional methods (M = 70.2). In contrast, pretest scores between the two groups were nearly equal. The statistical analysis confirmed that digital media had a more substantial effect on improving learning outcomes than conventional media. These findings support multimedia learning theories and highlight the importance of interactive and student-centred digital environments. In conclusion, digital learning media offer significant advantages in promoting students’ academic achievement and should be increasingly integrated into classroom instruction. Future research should explore its long-term effectiveness and adaptability in different contexts. Educational institutions are encouraged to invest in teacher training and infrastructure to support technology-based learning.